Genetic assortative mating for schizophrenia and bipolar disorder - Oskar Hougaard Jefsen; Ron Nudel; Yunpeng Wang; Jonas Bybjerg-Grauholm; Nicoline Hemager; Camilla A. J. Christiani; Birgitte K. Burton; Katrine S. Spang; Ditte Ellersgaard; Ditte L. Gantriis; Kerstin Jessica Plessen; Jens Richardt M. Jepsen; et al. (European Psychiatry, 2022)
Abstract